Chemically assisted physical sputtering of Tungsten: Identification via the 6Π→6Σ+ transition of WD in TEXTOR and ASDEX Upgrade plasmas. (January 2019) - Brezinsek, S.; Pospieszczyk, A.; Sergienko, G.; Dux, R.; Cavedon, M.; Faitsch, M.; Krieger, K.
Abstract: Tungsten ( W ) is a preferred plasma-facing material for areas of high particle and power impact in present day and future fusion devices. The lifetime of W plasma-facing components (PFCs) under steady-state conditions is limited by erosion processes induced by energetic impinging particles such as impurities (carbon C, oxygen O, nitrogen N, etc.) and hydrogen isotopes above the threshold energy for Physical Sputtering (PS ). We discovered for the first time, in addition to the bare physical sputtering process of W, a second W erosion mechanism at PFCs in TEXTOR (limiter surfaces) and ASDEX Upgrade (divertor target plates) during deuterium plasma bombardment. The tungsten deuteride molecule WD has been identified spectroscopically via the 6 Π → 6 Σ + transition in parallel to ordinary neutral W line emission of the WI transition (5 d 5 ( 6 S )6 s   7 S 3  → 5 d 5 ( 6 S )6 p   7 P 4 ) at λ = 400.9 nm used as measure to quantify the bare PS process or, more precisely, the gross erosion of W . We identified the underlying process for the molecular release as Chemically Assisted Physical Sputtering (CAPS ) as observed also in the case of beryllium or lanthanum. Measurements in TEXTOR and ASDEX Upgrade showed a dependence of the WD band emission on the surface temperature - connected to the deuterium content in the near W surface - as well as on the flux and energy of impinging energetic particles. A quantification of the released WD is not yet possible due to lack of appropriate molecular data for the conversion of photons into particles, but the spatially resolved ratio of atomic ( WI ) and molecular photon flux ( WD ) indicates that the release takes place at the same time, but differently distributed along the target plates and limiters reflecting the variation in the described critical parameters (impinging ion flux, ion impact energy, and material temperature) along the surface. The plasma conditions in front of the interaction zone are in both cases fully ionising with an electron temperature Te  > 10 eV, thus, recombination into WD can be excluded.